Draft Fifth Five Year Plan 1974-79 Rajasthan - Planning Commission (Planning Commission, 1974)
The objective of the Fifth Five Year Plan in Rajasthan is to strengthen the economic base by promoting development in the sectors which are capable of generating growth, and to ensure that the benefits of economic development are spread over a wider section of the population and that there is a significant improvement in the standard of living of the majority of the population, specially in the rural areas.
Planning Department, Government of Rajasthan